Expertise and purposeful activation of neck muscles modulate impact biomechanics in simulated soccer heading - a pilot study - Kern, J.; Gulde, P.; Hermsdörfer, J. (dvs-Biomechanik 2023 Tagungsband, 2023)
Within recent years, the topic of the potentially adverse effects of soccer heading on brain health has gained noticeable attention in both scientific research and sports practice. With respect to the latter, arguments concerning a ban or limitation of soccer heading in order to protect the players are opposed to the opinion that a correct technique is essential and that heading should be taught to players from a young age (Peek et al., 2020). While neck strength has been identified as a key factor contributing to a reduction of head impact severity (Gutierrez et al., 2014), the relationship between soccer experience, anticipatory activation of neck muscles, and head impact magnitude remains unknown. Therefore, the aim of this pilot study was to examine the effects of soccer expertise and neck stiffness on head impact biomechanics during header-related impacts.